1970
DOI: 10.1126/science.169.3951.1213
|View full text |Cite
|
Sign up to set email alerts
|

Tilorone Hydrochloride: An Orally Active Antiviral Agent

Abstract: Tilorone hydrochloride, 2,7-bis[2-(diethylamino)ethoxy]fluoren-9-one dihydrochloride, given orally to mice before they are infected is active against at least nine viruses of both RNA and DNA groups. The compound is effective when given prophylactically; the optimum time of treatment depends on the route of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
74
0
2

Year Published

1972
1972
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(77 citation statements)
references
References 0 publications
0
74
0
2
Order By: Relevance
“…When tested in vitro the three compounds possessed EC 50 values 230–420 nM, much lower than the positive control chloroquine (EC 50 4.0 μM) used in this study and identified previously 3 . Tilorone is an investigational agent that has been known for over 40 years as an antiviral 56 and is an inducer of interferon in mice 57 . It has been shown to possess a broad array of biological activities including cell growth inhibition in PC3 CDK5dn prostate cancer cells (IC 50 8–12 μM) 58 , inhibition of Primase DnaG from Bacillus anthracis (IC 50 7.1 μM) 59 , in a mouse model of pulmonary fibrosis it decreased lung hydroxyproline content and the expression of collagen genes 60 , α7 nicotinic receptor (nAChR) agonist activity (K i 56 nM) 61 , activated human alpha7 nAChR with an EC 50 value of 2.5 μM 62 , radioprotective activity 63 , potent modulation of HIF-mediated gene expression in neurons with neuroprotective properties 64 and induction of the accumulation of glycosaminoglycans, delay infectious prion clearance, and prolong prion disease incubation time 65 .…”
Section: Discussionmentioning
confidence: 99%
“…When tested in vitro the three compounds possessed EC 50 values 230–420 nM, much lower than the positive control chloroquine (EC 50 4.0 μM) used in this study and identified previously 3 . Tilorone is an investigational agent that has been known for over 40 years as an antiviral 56 and is an inducer of interferon in mice 57 . It has been shown to possess a broad array of biological activities including cell growth inhibition in PC3 CDK5dn prostate cancer cells (IC 50 8–12 μM) 58 , inhibition of Primase DnaG from Bacillus anthracis (IC 50 7.1 μM) 59 , in a mouse model of pulmonary fibrosis it decreased lung hydroxyproline content and the expression of collagen genes 60 , α7 nicotinic receptor (nAChR) agonist activity (K i 56 nM) 61 , activated human alpha7 nAChR with an EC 50 value of 2.5 μM 62 , radioprotective activity 63 , potent modulation of HIF-mediated gene expression in neurons with neuroprotective properties 64 and induction of the accumulation of glycosaminoglycans, delay infectious prion clearance, and prolong prion disease incubation time 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Tilorone hydrochloride, the orange, watersoluble dihydrochloride salt of 2,7-bis[2-(diethylamino) ethoxy] fluoren-9-one, is a broadspectrum antiviral agent (5). In mice, it is effective against Semliki Forest virus by the oral, subcutaneous, and intraperitoneal treatment routes.…”
mentioning
confidence: 99%
“…Tilorone, (2,7-bis[2-(diethylamino)ethoxy]-9H-fluoren-9-one), was discovered in 1970 as the first low molecular-weight IFN-inducing agent, effective in vivo against several DNA and RNA viruses in connection with its DNA intercalating property. [3][4][5] In fact, the mechanism of action of tilorone is related to DNA-intercalation induced by the two main components of the drug: the chromophore and the side chains. 6 Intercalation alters DNA chemo-physical properties stimulating cytokines expression 7 .…”
Section: Introductionmentioning
confidence: 99%